Association of Severity of Diabetic Foot Ulcer with Glycated Hemoglobin A1C Levels : Diabetic Foot Ulcer with Glycated HBA1C Levels - Din, Nizamud; Khan, Mahnoor; Danyal Khan, Bakht; Ghaffar, Tahir; Tabish Ikram, Muhammad; Aamir Salman , Muhammad; Khan Hadi, Niktash; Khan, Shafiullah (Pakistan Journal of Health Sciences, 2023)
Diabetic foot ulcer is a well-documented complication of uncontrolled diabetes and its association with the variables involved in Diabetes like FBS, RBS and HBA1C has been thoroughly researched. This research aims to identify the association of diabetic foot ulcer under Wagner classification with HBA1C classes. Objectives: To determine the severity of diabetic foot ulcer at various level of HBA1C and determine the association. Methods: A cross-sectional study with 360 diabetic patients who after giving consent filled questionnaires. The information was analyzed using SPSS v26 (IBM) through Chi Square test. The results were tabulated and inferred from. Results: Our work depicts a statistically significant correlation between grades of diabetic foot ulcer and HBA1C levels of the patients (p-value <0.001). Patients with higher levels of HBA1C suffered foot ulcer of higher grades. Specifically, patients with Grade 1 foot ulcers primarily had HBA1C levels of ≤ 11.00 with 6(50%) falling in the group “7.01-9.00” while patients with Grade 5 ulcers had higher HBA1C levels with bulk of patients having levels of >11.00. Conclusions: This research further supplemented an already strongly established association between uncontrolled diabetes and diabetic foot ulcer. We focused on specifically HBA1C and how increased lab values are linked with different grades of Diabetic Foot ulcer and found a strong association demanding a proactive approach towards patient care and education